2001
DOI: 10.1080/10473220116794
|View full text |Cite
|
Sign up to set email alerts
|

Development of Sampling and Analytical Methods for Concerted Determination of Commonly Used Chloroacetanilide, Chlorotriazine, and 2,4-D Herbicides in Hand-Wash, Dermal-Patch, and Air Samples

Abstract: Sampling and analytical methods were developed for commonly used chloroacetanilide, chlorotriazine, and 2,4-D herbicides in hand washes, on dermal patches, and in air. Eight herbicides selected for study were alachlor, atrazine, cyanazine, 2,4-dichlorophenoxyacetic acid (2,4-D), metolachlor, simazine, and two esters of 2,4-D, the 2-butoxyethyl ester (2,4-D, BE) and the 2-ethylhexyl ester (2,4-D, EH). The hand-wash method consisted of shaking the worker's hand in 150 mL of isopropanol in a polyethylene bag for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…From the above discussion of the reported studies, it can be concluded that the present method, which involves the gas chromatographic-mass-spectrometric electron impact ionization mode, simultaneous and rapid determination, has many advantages over the previously reported individual methods [8][9][10][11]. Data presented in Table 6 show the method to be a simultaneous determination of eight 1,3,5-triazine2,4 diamine herbicides and more sensitive than other techniques as reported in the literature [68][69][70][71][72][73][74][75][76][77][78][79]. In the present study, a high recovery rate and very low detection limits fill the gap towards an analytical method development for the simultaneous determination of residues of different structurally similar 1, 3, and 5-triazine compounds present in the water bodies.…”
Section: Resultsmentioning
confidence: 58%
“…From the above discussion of the reported studies, it can be concluded that the present method, which involves the gas chromatographic-mass-spectrometric electron impact ionization mode, simultaneous and rapid determination, has many advantages over the previously reported individual methods [8][9][10][11]. Data presented in Table 6 show the method to be a simultaneous determination of eight 1,3,5-triazine2,4 diamine herbicides and more sensitive than other techniques as reported in the literature [68][69][70][71][72][73][74][75][76][77][78][79]. In the present study, a high recovery rate and very low detection limits fill the gap towards an analytical method development for the simultaneous determination of residues of different structurally similar 1, 3, and 5-triazine compounds present in the water bodies.…”
Section: Resultsmentioning
confidence: 58%